La creación de la Escuela de Artes Dramáticas de la Universidad de Costa Rica - Fumero Vargas, Patricia (2016)
This article examines the creation of the School of Dramatic Arts and the process of reorganizing the Drama Section at the University of Costa Rica. I also address the cultural policies related to the creation of the Chamber Theatre ‘El Arlequín’ as well as the University Theatre Regulation issued in 1956.